6 - Locating Kenyan Media in Anti-Rape Discourse: A Feminist Critique - Lyn Ossome, (Africa Media Review, 2013)
The tendency in most African media to sensationalise sexual and gender-based violence abstracts this issue from the reality of its prevalence, and at the same time averts critical engagement with the social, political and economic contexts within which sexual violence occurs in society. This paper applies a critical feminist analysis to media coverage of sexual violence that has been observed during key moments in Kenya’s political history. The paper draws from representations of sexual violence reported in the media at various epochs during Kenya’s transition from colonialism and authoritarianism towards democracy and elections, and through these narratives, attempts to construct a theoretical framework within which the relationship that exists between women in Kenya and the (democratising) state might be analysed. The paper shows that anti-rape discourses were produced in the media but served different purposes than that of pursuing a feminist agenda, depending on the imperatives of the time in Kenya’s historical political development.